Optimizing Scan Range in Computed Tomography of Kidneys, Ureters, and Bladder: A Retrospective Study on Reducing Overscanning - Ali Bin Owien; Khaled Alenazi; Ahmad Abanomy; Mansour Almanaa; Mohammad Alarifi; Haitham Alahmad (Medicina)
Background and Objectives: Computed tomography of the kidneys, ureters, and bladder (CT KUB) is essential for evaluating urinary stones but also exposes patients to significant radiation. The scanning field should be minimized to only the necessary area to limit this radiation exposure. This study aims to assess the extent of CT KUB overscanning in renal colic procedures and identify the appropriate vertebral level for starting CT KUB scans. Materials and Methods: A retrospective analysis of 299 adult patients who underwent CT KUB examinations for kidney stone assessment was performed. To assess overscanning, the number of excess slices above the pole of the highest kidney and under the pubic symphysis was measured on the axial image of each patient. To allow for potential human error, a maximum acceptable level of overscanning was set at 10%. Results: This study found that only 31% of the scans met the target of less than 10% of overscanning superior to the highest kidney and inferior to the pubic symphysis. In comparison, overscanning was present in 69% of the scans, mainly at a superior level, resulting in higher radiation exposure for patients. Conclusions: A significant number of the scans exhibited unnecessary overscanning beyond the highest kidney, prompting us to propose using the upper border of the T10 vertebral body as a potential reference point to establish the upper margin for a CT KUB scan. This study suggests using T10 and the pubic symphysis as reliable landmarks to accurately determine the scan length. Starting CT KUB scans from the T10 vertebral body to the pubic symphysis allows for imaging of the entire urinary tract, minimizing unnecessary overscanning and reducing patient irradiation.